1982
DOI: 10.1017/s0043174500026199
|View full text |Cite
|
Sign up to set email alerts
|

Oximes as Seed Safeners for Grain Sorghum (Sorghum bicolor) to Herbicides

Abstract: Studies in growth chambers indicated that CGA-43089 {α-[(cyanomethoxy)imino] benzeneacetonitrile} applied at a rate of 1.25 g/kg of seed reduced the phytotoxicity of metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamide], bensulide [o,o-diisopropyl phosphorodithioateS-ester withN-(2-mercaptoethyl) benzenesulfonamide], EPTC (S-ethyl dipropylthiocarbamate), UBI-S734 {2-[(1,2,5-dimethylphenyl)ethylsulfonyl] pyridineN-oxide} and MBR-18337 {N-[4-(ethylthio)-2-(trifluoromethyl)phenyl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The initial slight injury of sorghum seedlings by metolachlor in the presence of the protectant CGA-43089 may be overcome by the plants later. Other investigators (2,29) have reported that, at the end of the growing season, the yields of sorghum plants protected with CGA-43089 and treated with metolachlor were equal or even better than those of the controls.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The initial slight injury of sorghum seedlings by metolachlor in the presence of the protectant CGA-43089 may be overcome by the plants later. Other investigators (2,29) have reported that, at the end of the growing season, the yields of sorghum plants protected with CGA-43089 and treated with metolachlor were equal or even better than those of the controls.…”
Section: Resultsmentioning
confidence: 94%
“…Today, the use of herbicide antidotes or crop protectanrs is an accepted practice in modern weed -management programs (1,22). CGA -43089 is a recently introduced herbicide antidote that enables grain sorghum to tolerate metolachlor and other acetanilide herbicides (2,4,5,6,13,19,21,26). Extensive evaluations under field conditions revealed that seed dressings with 1.25 and 1.5 g of CGA-43089/kg of seed protected sorghum against injury from metolachlor applied at rates as high as 4.0 kg/ha (6).…”
Section: Introductionmentioning
confidence: 99%
“…The oxime and aldehyde derivatives tested, in terms of decreasing safening effectiveness, were dimethyglyoxime > benzophenone oxime > pyridine-2-aldoxime > benzoin--oxime > methyl thioacetohydroxamate >pyridine-2-aldoxime methiodide > 5-nitro-furancarboxyaldehyde [22]. CAMM evaluations of the oxime ether analogues cyometrinil, oxabetrinil and fluxofenim revealed that as the effectiveness of the safener increases so does its molecular similarity to metolachlor [20].…”
Section: Structure-safening Activity Relationshipsmentioning
confidence: 99%
“…The first commercialized herbicide safener, 1,8-naphthalic anhydride (NA), was discovered in 1978 by Hoffman et al and was used to protect corn from thiocarbamate herbicide damage [13][14][15][16]. Synthetic herbicide safeners such as fenclorim, dichlormid, flurazole, fenchlorazole, and dymrone have since been commercialized for crop protection [17][18][19][20]. However, some commercially available herbicide safeners (e.g., dichlormid, benoxacor, and furilazole) are toxic to both aquatic organisms and mammals [21].…”
Section: Introductionmentioning
confidence: 99%